Optimizing Solar Panel Performance Using a Dual-Axis Solar Tracker Based on Fuzzy Control - Satria, Beni (CV Raskha Media Group, 2025)
The main problem with using static solar panels is the low energy efficiency due to changes in the sun's angle throughout the day, especially in tropical regions like Indonesia which have high solar energy potential. This study aims to optimize solar panel performance by designing a dual-axis solar tracker system based on fuzzy logic control to maintain the panel's orientation always perpendicular to sunlight. The research method includes mathematical modeling of the sun's position (elevation and azimuth), design of Mamdani fuzzy control with angle error inputs, and numerical simulation comparing daily irradiance and energy between static panels and the tracking system. Simulation results show a 33.15% increase in daily energy for the tracker system (11,983.33 Wh/m²) compared to static panels (8,999.65 Wh/m²), with the highest improvement occurring in the morning and evening. Fuzzy control provides smooth and stable movement response without excessive oscillation. These results prove that the dual-axis fuzzy-based solar tracker is effective in improving solar panel efficiency in tropical regions, although cost and mechanical complexity factors need to be considered in its implementation.